Is ChatGPT ready to change mental healthcare? Challenges and considerations: a reality-check - Pandya, Apurvakumar; Lodha, Pragya; Ganatra, Amit (Frontiers in Human Dynamics, 2024)
As mental healthcare is highly stigmatized, digital platforms and services are becoming popular. A wide variety of exciting and futuristic applications of AI platforms are available now. One such application getting tremendous attention from users and researchers alike is ChatGPT. Chat Generative Pre-trained Transformer (ChatGPT) is a powerful chatbot launched by Open Artificial Intelligence (Open AI). ChatGPT interacts with clients conversationally, answering follow-up questions, admitting mistakes, challenging incorrect premises, and rejecting inappropriate requests. With its multifarious applications, the ethical and privacy considerations surrounding the use of these technologies in sensitive areas like mental health should be carefully addressed to ensure user safety and well-being. The use of ChatGPT in mental healthcare raises various ethical considerations that need dire attention. The authors comment on the ethical challenges with ChatGPT in mental healthcare that need attention at various levels, outlining six major concerns viz., ( 1) accurate identification and diagnosis of mental health concerns; (2) safety, and security of users; (3) lack of evidence of efficacy; lack of monitoring and regulation; privacy concerns of open software; and research gap in training.